Emm type distribution of group A Streptococcus in China during 1990 and 2020: a systematic review and implications for vaccine coverage - Xiang, Caixin; Zhang, Jianzhong; Zhao, Fei; You, Yuanhai (Frontiers in Public Health, 2023)
Background The recent increase of group A Streptococcus (GAS) infections in Europe has aroused global concern. We aim to provide molecular biological data for GAS prevention and control in China by analyzing the temporal shift of emm type. Methods We collected studies reporting GAS emm types in China from 1990 to 2020 by PRISMA statement and established a summary database including emm types and literature quality assessment. Based on the database we analyzed the geographic distribution of emm types from 1990 to 2020 and assessed the coverage of the known GAS 30-valent vaccine. Outbreak-associated emm types that had been reported over the past 30 years were also included. Results 47 high quality studies were included for a systematic analysis of emm type distribution. This generated a database including totally 12347 GAS isolates and 85 emm types. Shift of dominant emm type was witnessed during the past thirty years in China. In mainland China, dominant types changed from emm3, emm1, emm4, emm12 in 1990s to emm12 and emm1 in 2000s and 2010s. Hong Kong and Taiwan were dominated by emm12, emm4 and emm1, of which emm4 reduced but emm12 increased in 2010s significantly. From 1990 to 2020, newly found emm types were increasingly reported in various regions of China. The reported 30-valent M protein vaccine covered 26 M types prevalent in China, including all dominant types. Conclusion Emm12 increased significantly in the past thirty years in China. The prevalent type of Hong Kong and Taiwan is slightly different from that of mainland China by emm4. Our long-term retrospective analysis implicates that the 30-valent M-protein vaccine can cover all dominant emm types prevalent in the past thirty years in China, which provide important basic data for future vaccine evaluation.